DETERMINANTS OF THE QUALITY OF LIFE OF PULMONARY TUBERCULOSIS (PTB) PATIENTS IN SURABAYA CITY - Eppy Setiyowati; Umi Hanik; Diba Adiba; Elok Mazida Mazida; Ratna Sri Wahyuni; Feri Agus Andriawan; Siti Hardianti (Universitas Nahdlatul Ulama Surabaya, 2020)
Tuberkulosis (TB) is an infectious disease caused by Mycobacterium tuberculosis, which can attack various organs, especially the lungs. The infectius disease untreated or treatment is not complete can causing complications dangerous until death. TB estimated to have existed in the world since 5000 BC, but advances in the discovery and control of new TB disease occurred in 2 of the last century. This study aimed determinant of quality of life in patients with pulmonary TB in Surabaya Type a descriptive research with survey approach on three large health centers with a total population sample of 150 respondents. The variable determinant of quality of life includes the respondents perception of the disease, health care search is done, the meaning of life for the respondents, satisfaction with family and health care. Data were collected through questionnaires, through purpusive sampling techniques, then performed the frequency distribution and crostabulasi. The results showed that the respondents' perceptions of the disease is mostly 78.4% said the illness as a result of the process of transmission of TB bacteria mycobaterium, the search for health services 95.7% went to the clinic, the meaning of life for themselves 78.6% said there was no hope for healed, satisfaction with family 67.5% are satisfied with the spirit given by family members and satisfaction of health workers say 85.3% are satisfied with the services provided by a health worker. The conclusion shows that detrminan quality of life in patients with pulmonary tuberculosis have searched for health services to the health service, satisfied with the health workers, but there is no hope of life to recover. Suggestions for further research to dig deeper into the life expectancy of the respondents